2015
DOI: 10.1097/nrl.0000000000000053
|View full text |Cite
|
Sign up to set email alerts
|

Increased Serum Brain-derived Neurotrophic Factor in Multiple Sclerosis Patients on Interferon-β and Its Impact on Functional Abilities

Abstract: This study showed a significant effect of interferon-β 1b therapy on increasing BDNF production in multiple sclerosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

2
6
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 27 publications
2
6
0
Order By: Relevance
“…Our results are in agreement with a recent study showing that INF-beta can increase serum BDNF levels [27] and with a previous study demonstrating an increased production of BDNF by peripheral blood mononuclear cells following stimulation with INF-beta [28]. Serum levels of BDNF varies during to the different phases of RR-MS.…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…Our results are in agreement with a recent study showing that INF-beta can increase serum BDNF levels [27] and with a previous study demonstrating an increased production of BDNF by peripheral blood mononuclear cells following stimulation with INF-beta [28]. Serum levels of BDNF varies during to the different phases of RR-MS.…”
Section: Discussionsupporting
confidence: 93%
“…It is worth to mention also the current debate regarding the significance of serum BDNF levels in terms of biomarker of disease progression. Mehrpour et al [27], proposed serum BDNF with levels above a cut-off of 190 pg/ml as a biomarker of disease severity, while in another study, serum BDNF levels did not seem to correlate with the extent of neurodegeneration [33]. Besides the current difficulties in dissecting out the exact correlation between BDNF levels and phase or severity of the disease, our findings are in support of a possible neurotrophic effect of INF-beta in SM.…”
Section: Discussionsupporting
confidence: 56%
“…As for beta-interferons, they were also shown to influence BDNF levels in vivo. Mehrpour et al found increased serum BDNF levels in MS patients on beta-interferons, as opposed to patients on mitoxantrone or receiving no immunotherapy [24]. Moreover, they found that higher BDNF levels were associated with smaller disability in their MS cohort.…”
Section: Discussionmentioning
confidence: 98%
“…On the other hand, other studies revealed increased serum BDNF levels in multiple sclerosis patients during interferon beta therapy [25,28,34,35]. The difference between results may be attributed to the different sample sizes, noncompliance of patients, half of our patients were in relapse, and some of them received monthly methylprednisolone.…”
Section: Discussionmentioning
confidence: 64%